Proactivity: influence of conditions for creativity considering and the mediating effect of creative self-efficacy - Veiga, Heila Magali da Silva; Neiva, Elaine Rabelo; Bruno-Faria, Maria de Fátima (Revista de Administração da UFSM, 2020)
The main goal of this study was to investigate the influence of the perception of favorable (manager support, challenging activities, strategy, coworkers, freedom, and physical environment) and unfavorable conditions (manager inadequate attitude, rules, and lack of time) for creativity upon the criterion variable, proactivity, taking into account the mediating effect of “Creative Self-Efficacy (CSE)”. A convenience sample of 297 participants from different organizations took part in this study and the model proposed was tested through the modeling of structural equations, employing the individual level of analysis. The findings have shown that all the dimensions of the aforementioned variable make a significant contribution to proactivity, with the highest contribution being the manager support. The mediating hypothesis has shown that CSE mediates the relationship between the favorable conditions for creativity (manager support, challenging activities, strategy, and coworkers) and proactivity, indicating that the influence of context in proactivity is maximized by CSE.